PANCHAYATS AS CATALYSTS FOR RURAL HEALTHCARE: INTEGRATING TELEMEDICINE AND CONFLICT RESOLUTION IN INDIA - Rajesh, Molagavalli (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The Panchayat system, a cornerstone of rural governance in India, has long been recognized for its role in conflict resolution and community development. In recent years, there has been growing interest in leveraging Panchayats to address healthcare challenges and mediate health-related disputes in rural areas. This research article explores the intersection of healthcare delivery and conflict management through Panchayats, with a special focus on the role of telemedicine in promoting healthcare equity. Drawing on case studies and existing literature, the article examines the strengths, challenges, and opportunities of integrating healthcare, telemedicine, and conflict resolution within the Panchayat framework. It concludes with recommendations for strengthening Panchayats to better serve rural communities in India.